2022
DOI: 10.1021/acssynbio.2c00013
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Antisense Oligonucleotides as Antibacterial Agents That Target FMN Riboswitches and Inhibit the Growth of Staphylococcus aureus, Listeria monocytogenes, and Escherichia coli

Abstract: In the past several decades, antibiotic drug resistance has emerged as a significant challenge in modern medicine due to the rise of many bacterial pathogenic strains resistant to all known antibiotics. At the same time, riboswitches have emerged as novel targets for antibacterial drug discovery.Here for the first time, we describe the design and applications of antisense oligonucleotides as antibacterial agents that target a riboswitch. The antisense oligonucleotides are covalently coupled with two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…ASO-1 is delivered into the bacterial cells by a non-toxic oligopeptide (pVEC) derived from the murine vascular endothelial-cadherin protein, which is degraded by peptidases after its entry into the cells. The ASO-1/FMN aptamer hybrid is recognized and cleaved by RNase H. Strikingly, ASO-1 at the same concentration showed a bacteriostatic effect against S. aureus , L. monocytogenes , and E. coli with MIC 80 700 nM and non-toxic effect in the lung cancer A549 cell line [ 62 ]. Antisense oligonucleotides seem to be promising antimicrobial agents due to their straightforward design, as well as their convenient cellular delivery.…”
Section: Fmn Riboswitchesmentioning
confidence: 99%
“…ASO-1 is delivered into the bacterial cells by a non-toxic oligopeptide (pVEC) derived from the murine vascular endothelial-cadherin protein, which is degraded by peptidases after its entry into the cells. The ASO-1/FMN aptamer hybrid is recognized and cleaved by RNase H. Strikingly, ASO-1 at the same concentration showed a bacteriostatic effect against S. aureus , L. monocytogenes , and E. coli with MIC 80 700 nM and non-toxic effect in the lung cancer A549 cell line [ 62 ]. Antisense oligonucleotides seem to be promising antimicrobial agents due to their straightforward design, as well as their convenient cellular delivery.…”
Section: Fmn Riboswitchesmentioning
confidence: 99%
“…In vitro experiments in Penchovsky’s laboratory with antisense oligonucleotides, for the first time designed with cell-penetrating peptides and targeted to GlmS [ 44 ] and FMN riboswitches [ 45 ] in three different bacteria, demonstrated that our previous genome-wide bioinformatics results [ 8 ] were proved true and could be used as a milestone for the antisense technology for antibacterial drug development.…”
Section: Resultsmentioning
confidence: 99%
“…Following the logic of our previous research for the genome-wide analyses of the riboswitches TPP, FMN, GlmS, lysine, cobalamin, SAM, SAH, adenine, and guanine, we grouped the riboswitches into four categories based on their suitability as antibacterial drug targets [ 8 , 44 , 45 , 50 ]. The ‘Most suitable riboswitches’ group controls the unique, essential biosynthetic pathway and the ‘Very suitable riboswitches control the essential biosynthetic pathway and protein transporter for the key metabolites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations